2013
DOI: 10.1371/journal.pgen.1003676
|View full text |Cite
|
Sign up to set email alerts
|

The Genome of Spraguea lophii and the Basis of Host-Microsporidian Interactions

Abstract: Microsporidia are obligate intracellular parasites with the smallest known eukaryotic genomes. Although they are increasingly recognized as economically and medically important parasites, the molecular basis of microsporidian pathogenicity is almost completely unknown and no genetic manipulation system is currently available. The fish-infecting microsporidian Spraguea lophii shows one of the most striking host cell manipulations known for these parasites, converting host nervous tissue into swollen spore facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
88
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(95 citation statements)
references
References 65 publications
6
88
1
Order By: Relevance
“…Two ricin B lectin-like secreted proteins were also identified in the supernatant of germinated Spraguea lophii spores [9]. Some research showed that lectins play diverse roles in parasites such as mediating parasite adhesion to host cell during infection, mediating immune evasion, and triggering different developmental pathways in the parasite [56,57].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two ricin B lectin-like secreted proteins were also identified in the supernatant of germinated Spraguea lophii spores [9]. Some research showed that lectins play diverse roles in parasites such as mediating parasite adhesion to host cell during infection, mediating immune evasion, and triggering different developmental pathways in the parasite [56,57].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, spore germination may play a major role in host invasion, and the elucidation of spore germination will provide some valuable information for understanding the whole invasion process. Some genomes of important microsporidia have been reported and analyzed [7][8][9]. Based on the understanding of the microsporidia genome, transcriptome studies have been widely carried out [9][10][11], which generated information on the changes of total mRNA during a particular period.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, HGT into fungi was thought to be rare, but several examples from bacteria into fungi or between fungi have recently been described (5,8,9). For example, one phylum of early-diverging fungi, the Microsporidia, has had a handful of HGT events documented (5,(10)(11)(12), but these fungi are thought to have acquired relatively few genes through HGT (13).…”
mentioning
confidence: 99%
“…Known HGT events into Microsporidia include the following: (i) the ADP/ATP translocase gene family, originating from an HGT event that transferred the founding gene from a member of the bacterial phylum Chlamydia (10), which are known to steal energy-bearing molecules from their host; (ii) a sixgene folate synthesis pathway transferred into Encephalitozoon hellem from multiple donors, a transfer hypothesized to reduce host metabolic stress (11); and (iii) the acquisition of a glutamateammonia ligase from an unknown prokaryotic source by Spraguea lophii, which is thought to provide spores a mechanism for defense against the ammonia generated by the decomposing flesh in which they are embedded (12). These case studies, the first of which is shared with the Cryptomycota (19), suggest a role for HGT in the evolution of their unusual pathogenic metabolisms and indicate the need for a thorough, systematic analysis of HGT events in these early-diverging fungi.…”
mentioning
confidence: 99%